Spin rectification by planar Hall effect in synthetic antiferromagnets - Gonzalez Chavez, D. E.; Asmat Perve, M.; Aviles Felix, Luis Steven; Gomez, Javier Enrique; Butera, Alejandro Ricardo; Sommer, R. L. (Elsevier Science, 2022)
Fil: Gonzalez Chavez, D. E.. Centro Brasileiro de Pesquisas Físicas; Brasil